Pengaruh Firm Size, Likuiditas, Leverage Dan Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Sub Sektor Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia - Ferdila Ferdila; Ita Mustika; Sri Martina (Politeknik Ganesha Medan, 2023)
This study examines how business size, liquidity, leverage, and profitability affect firm value in Indonesia Stock Exchange-listed supply products manufacturing companies between 2019 and 2021. Earlier corporate value study had mixed results. Therefore, more research is needed to retest company worth. The survey sampled 47 consumer products manufacturers. For the three-year observation period (2019–2021), 13 business samples were purposefully sampled with 39 observations. The Indonesian Stock Exchange website provided the sample businesses and research data. Research data obtained from the Indonesian Stock Exchange website, where sample businesses were found. The data analysis approach began with descriptive statistics, classical assumption test, multiple regression analysis, and hypothesis testing. Corporate size, liquidity, leverage, and profitability affect firm value. According to research, only profitability increases firm worth significantly. Significant to firm value. Liquidity boosts corporate value but not significantly. Leverage and firm size have minimal impact on firm value